TRAINING OF MATHEMATICS TEACHING MATERIALS BASED ON ENTREPRENEURSHIP - Alpha Galih Adirakasiwi; Attin Warmi; Achmad Nawawi (JCES (Journal of Character Education Society), 2021)
Abstrak: Pembelajaran berbasis kewirausahaan bertujuan agar jiwa kewirausahaan dimiliki oleh setiap siswa yang lulus di satuan pendidikan dengan harapan jiwa kewirausahaan sebagai modal dasar dalam berwirausaha ketika mereka sudah lulus. Tujuan dari kegiatan ini adalah agar guru dan calon guru mendapatkan pemahaman sekaligus mempraktekan mengenai pembuatan bahan ajar berbasis kewirausahaan. Pelaksanaan pengabdian ini dilaksanakan pada tanggal 13-14 Oktober 2020 dengan jumlah peserta sebanyak 36 orang dari guru dan calon guru matematika. Kegiatan ini dilaksanakan di SMK Rosma Karawang. Hasil dari kegiatan ini menunjukan bahwa pelatihan pengembangan bahan ajar berbasis kewirausahaan ini ditanggapi positif oleh peserta pelatihan dengan kategori puas 52,6% dan sangat puas 47,4%. Peserta pelatihan memiliki wawasan baru mengenai pengembangan bahan ajar yang dapat diterapkan di kelas ketika pembelajaran dilaksanakan.Entrepreneurship-based learning aims to make an entrepreneurial spirit possessed by every student who graduates in the education unit with the hope that an entrepreneurial spirit is the basic capital in entrepreneurship when they graduate. The purpose of this activity is so that teachers and prospective teachers gain understanding as well as practice making entrepreneurship-based teaching materials. This service was carried out on October 13-14 2020 with a total of 36 participants from teachers and prospective mathematics teachers. This activity was carried out at SMK Rosma Karawang. The results of this activity showed that the entrepreneurship-based teaching materials development training received a positive response from the training participants with the category of 52.6% satisfied and 47.4% very satisfied. Training participants have new insights about the development of teaching materials that can be applied in class when learning is carried out.